Indocyanine green angiography for identifying telangiectatic capillaries in diabetic macular oedema. Issue 4 (29th July 2019) - Castro Farías, Daniela; Matsui Serrano, Rodrigo; Bianchi Gancharov, Juan; de Dios Cuadras, Ulises; Sahel, José; Graue Wiechers, Federico; Dupas, Benedicte; Paques, Michel
Abstract : Aims: During diabetic macular oedema (DME), a spectrum of capillary abnormalities is commonly observed, ranging from microaneurysms to large microvascular abnormalities. Clinical evidence suggests that targeted photocoagulation of large microvascular abnormalities may be beneficial, but their detection is not done in a routine fashion. It was reported that they are better identified by indocyanine green angiography (ICGA) than by fluorescein angiography. Here, we investigated the prevalence and ICGA and optical coherence tomography (OCT) features of retinal microvascular abnormalities in a group of patients with DME. Methods: Observational study. The fundus photographs, ICGA and structural and angiographic OCT charts of 35 eyes from 25 consecutive patients with DME were reviewed. Results: 22 eyes (63%) had at least one focal area of microvascular abnormalities showing prolonged indocyanine green (ICG) staining (ie, beyond 10 mins after injection). In particular, all eyes (n=9) with circinate hard exudates showed foci of late ICG staining. These areas were either isolated globular capillary ecstasies or a cluster of ill-defined capillary abnormalities. They were located at a median distance of 2708 µm from the fovea (range: 1064–4583 µm). Their diameter ranged from 153 to 307 µm. During ICGA, 91% showed increased their contrast and apparent size in late frames, whereas 79% of microaneurysms showed reduced contrast on late frames. OCT angiography was not contributive for the detection of these lesions. Conclusion: Late ICG staining revealing large microvascular abnormalities is commonly observed during DME. Because of their specific angiographic and OCT features relative to microaneurysms, we propose to name them telangiectatic capillaries (TelCaps).